Implementation and Performance Evaluation of Occupational Health and Safety Management Systems in a Building Construction Project - Hendra Hendra; Heru Pramanda; Dedek Ariansyah; Bunyamin Bunyamin; M Reza Hani (Popular Scientist, 2026)
Occupational Health and Safety Management Systems (OHSMS) represent a managerial approach designed to protect workers from occupational accidents and work-related diseases, thereby creating a safe, efficient, and productive working environment. Nevertheless, the increasing number of occupational accidents in Indonesia, as reported by the Social Security Administration for Employment, indicates that the implementation of such systems continues to face significant challenges in practice. The primary issue addressed in this study is the limited understanding of hazard potential, the level of occupational risk, and the effectiveness of risk supervision and control in building construction projects. Therefore, this research aims to analyze the implementation of the Occupational Health and Safety Management System, identify high-risk construction activities, and evaluate the factors contributing to potential workplace accidents in the Landmark BSI (Bank Syariah Indonesia) Building Construction Project in Aceh. This study employed a quantitative approach supported by statistical analysis. Primary data were collected through field observations, questionnaire surveys administered to respondents, and project documentation, while secondary data included project organizational structures and workforce information. The findings reveal that the implementation of occupational health and safety management practices in the Landmark BSI Aceh Building Construction Project can be categorized as relatively effective, as evidenced by the execution of hazard identification procedures, safety protocols, and risk control measures. However, improvements are still required in terms of supervision, consistency of implementation, and the strengthening of safety culture to sustainably minimize the potential for workplace accidents.